2019
DOI: 10.1136/bcr-2018-228806
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal diabetes mellitus: remission induced by novel therapy

Abstract: A female child with deafness was diagnosed to have neonatal diabetes mellitus at the age of 6 months, on routine evaluation prior to cochlear implant surgery. She presented to us at 11 months of age with diabetic ketoacidosis due to an intercurrent febrile illness. Her haematological parameters showed megaloblastic anaemia and thrombocytopenia. Therefore a possibility of Thiamine Responsive Megaloblastic Anaemia (TRMA) syndrome was considered. She was empirically treated with parenteral thiamine hydrochloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…NDM is diagnosed only in infants, primarily in the first three months after delivery and treated either insulin or drugs, and varies based on the affected gene, whereas T1DM can develop in all individuals, starting from children to adults; T1DM is caused by the failure of the pancreas to produce insulin. The prevalence of NDM and T1DM varies ( Dalwadi et al., 2019 ). Earlier studies have confirmed that NDM occurs due to reduced birth weight for gestational age ( Aguilar-Bryan and Bryan, 2008 ), while in T1DM, there is no connection with gestational birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…NDM is diagnosed only in infants, primarily in the first three months after delivery and treated either insulin or drugs, and varies based on the affected gene, whereas T1DM can develop in all individuals, starting from children to adults; T1DM is caused by the failure of the pancreas to produce insulin. The prevalence of NDM and T1DM varies ( Dalwadi et al., 2019 ). Earlier studies have confirmed that NDM occurs due to reduced birth weight for gestational age ( Aguilar-Bryan and Bryan, 2008 ), while in T1DM, there is no connection with gestational birth weight.…”
Section: Introductionmentioning
confidence: 99%